Real-time 16K video coding on a GPU with complexity scalable BPC-PaCo - de Cea-Dominguez, Carlos; Moure, Juan C.; Bartrina-Rapesta, Joan; Aulí-Llinàs, Francesc (Signal processing. Image communication, 2021)
The advent of new technologies such as high dynamic range or 8K screens has enhanced the quality of digital images but it has also increased the codecs’ computational demands to process such data. This paper presents a video codec that, while providing the same coding features and performance as those of JPEG2000, can process 16K video in real time using a consumer-grade GPU. This high throughput is achieved with a technique that introduces complexity scalability to a bitplane coding engine, which is the most computationally complex stage of the coding pipeline. The resulting codec can trade throughput for coding performance depending on the user’s needs. Experimental results suggest that our method can double the throughput achieved by CPU implementations of the recently approved High-Throughput JPEG2000 and by hardwired implementations of HEVC in a GPU.